PONV management in patients with QTc prolongation on the EKG - S. Soghomonyan; N. Stoicea; W. Ackermann; S. P. Bhandary (Frontiers Media S.A., 2021)
Postoperative nausea and vomiting (PONV) is a commonly encountered problem in surgical practice. It delays discharge from the post-anesthesia care unit, requires additional resources to treat, and may increase the morbidity in some patients. Many effective drugs are available to treat or prevent PONV, however many of these drugs have the potential to prolong the QTc on the electrocardiogram (EKG) and increase the risk of serious ventricular arrhythmias, in particular, torsade de pointes. The QTc prolongation may be a manifestation of a genetic mutation resulting in abnormal myocyte repolarization or it may be acquired and associated with the use of various medications, electrolyte disorders, and physiological conditions. Patients predisposed to QTc prolongation presenting for surgery constitute a challenging group, since many drugs commonly used for PONV management will put them at risk for perioperative serious arrhythmias. This is an important topic, and our mini-review is an attempt to highlight the problem, summarize the existing experience, and generate recommendations for safe management of PONV for patients, who are at increased risk of QTc prolongation and arrhythmias. Focused prospective studies will help to find definitive answers to the discussed problems and challenges and develop specific guidelines for clinical application.